Relationship between the asymmetry of the resting scapular position and the prevalence of latent myofascial trigger points in the trapezius muscle in asymptomatic adults - Yasuhiro Aki; Ippei Okino; Genki Tsuyama; Yoshiyasu Tanitsu; Hisao Nishijo; Kouichi Takamoto (PLoS ONE, 2025)
Myofascial trigger points (MTrPs) and body postural misalignment, including the position of the scapula, can contribute to the onset and persistence of musculoskeletal pain. However, the relationship in asymptomatic cases remains unclear. Therefore, this study aimed to investigate the relationship between the asymmetry of the resting scapular position and latent MTrPs in the upper trapezius muscle (UTM) in asymptomatic adults. A total of 32 asymptomatic adult men (mean age, 26.28 ± 1.1 years) were included in this study. Full-body photographs were taken from the posterior view, with the participants resting in a standing position. To determine the degree of asymmetry of the resting scapular position, the horizontal scapular alignment angle (HSAA) was analyzed from the photographs. The assessor identified the presence of latent MTrPs in the right and left UTMs. The HSAA was significantly lower in the group with latent MTrPs in the right UTM than in those without latent MTrPs. The results showed that the right scapula was more depressed than the left scapula in the group with latent MTrPs in the right UTM. Furthermore, multiple regression analysis indicated that the dominant arm and presence of latent MTrPs in the right UTM significantly contributed to the prediction of the HSAA. The results of this study demonstrated a close relationship between the asymmetry of the resting scapular position and latent MTrPs in the UTM in asymptomatic adults, which may contribute to the onset and persistence of musculoskeletal pain.